Hybrid and inclusive entrepreneurship as the determinants of self-employment: The mediating role of entrepreneurial atmosphere - Aaron A. Vargas Zeledon (Diponegoro International Journal of Business, 2022)
This study examines how hybrid entrepreneurship and inclusive entrepreneurship elucidate self-employment. In addition, consider the entrepreneurial atmosphere as a mediator. Using 118 country cases from Global Entrepreneurship Monitor and World Economic Forum Growth and Development Index employs a fuzzy-set qualitative comparative analysis (fsQCA) configuration approach embracing the phenomenon's complexity. This study advances the set-theoretic configuration by examining powerful, evocative terms. The findings of the analysis are as follows. First, both hybrid and inclusive entrepreneurship elucidate an important relationship with self-employment. Second, the elucidation of the terms varies according to the dissimilar economic context. Third, social norms and culture toward self-employment are a dominant influence to play a significant elucidation enabling hybrid entrepreneurship and inclusive entrepreneurship. This study distinguishes several valuable implications for academia, practitioners, and policymakers.